Peptides and Peptidomimetics as Potential Antiobesity Agents: Overview of Current Status - Kumar, Maushmi S. (Frontiers in Nutrition, 2019)
There is high occurrence of obesity but with very few new medications approved for treatment and the existing ones suffer from major side effects. Therefore new approaches to treat obesity needs an urgent attention. Bioactive peptides from food and marine organisms, apart from their anti-oxidant, anti-inflammatory, anti-microbial, and anti-viral activities have been used to treat metabolic disorders- such as type-2 diabetes and obesity. However, the development of these peptides has taken backstage due to their less stability, poor bioavailability, poor delivery, size, rate of degradation etc. But recently with the emerging newer techniques for developing multifunctional peptides, mimetics, peptide analogues and aptamers there is sudden revival in this therapeutic field. An increased attention is given upon developing the natural peptides from food sources that mimic the function of mediators involved in weight management to avoid obesity. Herein, we search for the structures of anti-obesity peptides and explore their potential as antiobesity agents. We have discussed endogenous, food and marine peptides to understand their current status and future scope. This review also provide the compiled overview of novel and interesting experimental approaches based on peptidomimetics for controlling obesity. We specifically examined apolipoprotein A-I (apoA-I), melanocortin-4 receptor (MC4R)-specific agonist, GLP-1 dual and triple agonists, neuropeptides, prolactin-releasing peptide mimetics. Novel peptides, mimetics and synthesis interventions are transpiring and might offer safer alternatives for otherwise scarcely available safe antiobesity drug. We require to understand more about peptides, their chemistry and engineering to overcome their disadvantages and select the best mimetics and analogues for treatment.